Earnings Retention, New Capital and the Growth of the Firm - Baumol, William J.; Heim, Peggy; Malkiel, Burton G.; Quandt, Richard E. (The Review of Economics and Statistics, 1970)
William J. Baumol, Peggy Heim, Burton G. Malkiel, Richard E. Quandt, Earnings Retention, New Capital and the Growth of the Firm, The Review of Economics and Statistics, Vol. 52, No. 4 (Nov., 1970), pp. 345-355